DISCURSOS NO YOUTUBE EM TORNO DAS DISSIDÊNCIAS SEXUAIS E DE GÊNERO - Carvalho, Rafael Silva de (2020)
This research is dedicated to problematize the discourses that are (re)produced in a network through a video clip and their comments on the internet, specifically, on the YouTube video platform, about the statements in dispute for the truths of sexual and